Pengetahuan, Sikap serta Respons Fisiologis dan Psikologis WUS tentang Kanker Serviks - Kusuma, Ratu (Universitas Baiturrahim, 2024)
Cervical cancer is one of the most common reproductive malignancies experienced by women after breast cancer. The incidence in Indonesia is ± 23.4 per 100,000 population (average death 13.9 per 100,000 population) and ± 80-90% are difficult to cure because the majority (>70%) of sufferers seek treatment at an advanced stage. This research aims to identify the knowledge, attitudes and physiological and psychological responses of women of childbearing age(WUS) regarding cervical cancer in the working area of the Puskesmas Koni, Jambi City. This is a narrative descriptive study with a cross sectional approach on 132 samples selected accidentally from the 852 WUS population. Research data collection was carried out in January 2022 using knowledge instruments and attitude instruments as well as unstructured interview guides to explore the physical and psychological responses of WUS regarding cervical cancer. Next, the data was analyzed using univariate analysis. The results of the study reported that 63.67% of WUS had poor knowledge about cervical cancer and 59.85% showed negative attitudes; 115 (87.12%) WUS were married but none of them had an IVA-test. The results of the identification of the physical response were that several WUS experienced symptoms of sexually transmitted infections in the form of pathological vaginal discharge with symptoms of yellowish, foul-smelling, itchy, lumpy vaginal secretions. Meanwhile, the psychological response of WUS is that they are embarrassed to carry out IVA tests or other examinations either at the Puskesmas Koni or other health facilities/health workers, and just let the vaginal discharge they experience go untreated. Another factor that may be related to this infection is a husband who is a user or a history of drug use. Thus, it is concluded that there is still low knowledge and poor attitudes of WUS regarding cervical cancer even though some WUS have symptoms of sexually transmitted infections in the form of pathological vaginal discharge.